TRI PUSAT PENDIDIKAN DAN MODERASI BERAGAMA: TELAAH FILOSOFIS ATAS GAGASAN KI HADJAR DEWANTARA - Jumahir Magfira; Hairuddin Cikka; Makmur (Mahiyah: Journal of Islamic Thought and Philosophy, 2026)
This study aims to philosophically analyze the concept of the Tri-Center of Education in the thought of Ki Hadjar Dewantara and its relevance in strengthening religious moderation in Indonesia. The research employs a qualitative method with a library research approach and philosophical analysis. Data sources include the original works of Ki Hadjar Dewantara, educational literature, and studies related to religious moderation. The findings reveal that the Tri-Center of Education—comprising family, school, and society—plays a strategic role in shaping individuals with moderate religious attitudes. The family serves as the foundation for value internalization, the school functions as a space for intellectual and moral development, and society acts as a practical arena for implementing these values. Philosophically, this concept is rooted in humanistic principles that emphasize balance, freedom, and respect for human dignity. These values align with the principles of religious moderation, such as tolerance, justice, and equilibrium. Therefore, the integration of the Tri-Center of Education can serve as an effective model for strengthening religious moderation and fostering harmonious social life in Indonesia’s multicultural society.